Local Wisdom of Tanjung Tanah Manuscript to Increase Historical Comprehension Ability - Lionar, Uun; Mulyana, Agus; Isrok'atun, Isrok'atun (History Department, Semarang State University and Historian Society of Indonesia, 2020)
Learning history in schools has always been based on the process of knowledge transfer, including memorizing textbooks. That kind of method has reduced essence historical thinking, especially in the ability to historical comprehension. For the process to successfully reconstruct knowledge, one way that can be done is to use the history book of local wisdom in ancient manuscripts. The Tanjung Tanah manuscript is one of the ancient documents which contains the value of local wisdom, such as the value of responsibility, respect, and honesty. Through history learning based on local wisdom of the Tanjung Tanah manuscript, it is expected that students will be able to comprehend historical comprehension more quickly. This study uses quantitative methods with a quasi-experimental design. The population is students at grade ten of senior high school in Kerinci Regency, while the sample is students at degree ten of SMA Negeri 2 Kerinci. The results of the study show that learning the history of local wisdom of Tanjung Tanah manuscripts improves the students’ historical comprehension ability.Pembelajaran sejarah di sekolah selama ini masih bertumpu pada proses transfer of knowledge berupa menghafal isi buku teks. Cara tersebut telah mereduksi esensi keterampilan berpikir sejarah, terutama pada kemampuan pemahaman sejarah. Agar terjadi proses reconstruct of knowledge maka salah satu cara yang dapat dilakukan adalah menghadirkan pembelajaran sejarah berbasis kearifan lokal dalam naskah-naskah kuno. Naskah Tanjung Tanah merupakan salah satu naskah kuno yang sarat nilai kearifan lokal, seperti nilai tanggung jawab, sikap hormat, dan kejujuran. Melalui pembelajaran sejarah berbasis kearifan lokal Naskah Tanjung Tanah diharapkan akan terjadi peningkatan kemampuan pemahaman sejarah pada siswa. Penelitian ini menggunakan metode kuantitatif kuasi eksperimen, populasi adalah siswa SMA kelas X di Kabupaten Kerinci, sampel siswa kelas X SMA Negeri 2 Kerinci. Hasil penelitian menunjukkan pembelajaran sejarah berbasis kearifan lokal Naskah Tanjung Tanah efektif meningkatkan kemampuan pemahaman sejarah siswa.